Strategic Marketing in the Era of Modernization - Rizki, Dwiki Fatur (Al Makki Publisher, 2023)
In the era of modernization influenced by technological developments and changes in consumer behavior, marketing strategies are the key to company success. This article discusses the importance of adapting marketing strategies in the face of modernization challenges, including digital transformation, globalization, and high consumer expectations. Up-to-date, data-focused, and customer-experience-oriented marketing strategies are key to maintaining a company's competitiveness in this ever-changing era. This article outlines some of the main factors that influence a company's marketing strategy in the context of the modernization era. First, technological developments and digitalization have changed the way consumers interact with brands and products. Therefore, companies must adapt quickly, utilize online platforms, and optimize their digital marketing strategies.